2007
DOI: 10.4049/jimmunol.178.2.1048
|View full text |Cite
|
Sign up to set email alerts
|

Distinct NKT Cell Subsets Are Induced by Different Chlamydia Species Leading to Differential Adaptive Immunity and Host Resistance to the Infections

Abstract: We investigated the role of NKT cells in immunity to Chlamydia pneumoniae and Chlamydia muridarum infections using a combination of knockout mice and specific cellular activation approaches. The NKT-deficient mice showed exacerbated susceptibility to C. pneumoniae infection, but more resistance to C. muridarum infection. Activation of NKT reduced C. pneumoniae in vivo growth, but enhanced C. muridarum infection. Cellular analysis of invariant NKT cells revealed distinct cytokine patterns following C. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 47 publications
3
109
0
Order By: Relevance
“…1C). It has been reported that ␥␦ T and NKT cells can also produce IL-17 (4,5), and we have shown that both types of these cells are activated by Cm infection (45)(46)(47). Therefore, it is worthwhile to test whether these cells also produce IL-17 and what cell(s) is the major source of the IL-17 produced during chlamydial infection.…”
Section: Discussionmentioning
confidence: 99%
“…1C). It has been reported that ␥␦ T and NKT cells can also produce IL-17 (4,5), and we have shown that both types of these cells are activated by Cm infection (45)(46)(47). Therefore, it is worthwhile to test whether these cells also produce IL-17 and what cell(s) is the major source of the IL-17 produced during chlamydial infection.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that determine whether a Th1 or a Th2 response develops following Chlamydia infection is largely unknown, but will be important to understand in order to develop a vaccine that will stimulate protective and not pathological outcomes. Recent experiments comparing immune responses against different species of Chlamydia have suggested that NKT cells may be an important determinant of the Th1/Th2 bias during Chlamydia infections (Joyee et al, 2007).…”
Section: Effector Functions Of Cd4 + T Cellsmentioning
confidence: 99%
“…The isolated CD4 + T cells were cocultured with purified DCs in the presence of ultraviolet-inactivated Cm as described (54). In designated experiments, anti-ICOS-L mAbs (10 μg/mL, clone HK5.3; eBioscience) were added to the coculture wells to block ICOS-L signal pathway (51).…”
Section: Dcs and Cd4 T-cell Purification And Dc/t-cell Coculturementioning
confidence: 99%
“…Spleen and lungs were aseptically removed. To analyze cytokine production, single-cell suspensions were prepared from spleen and lungs as described previously (53,54). The cells were cultured at a concentration of 7.5 × 10 6 cells/mL (splenocytes) or 5.0 × 10 6 cells/mL (lung cells), respectively, in complete culture medium with or without stimulation of ultraviolet-inactivated Cm (10 5 IFU/mL).…”
Section: In Vitro Restimulation Assays and Cytokine Measurementmentioning
confidence: 99%
See 1 more Smart Citation